THE DEVELOPMENT OF BW-EXPORT MODEL ON SCIENTIFIC LEARNING DEVICES TO IMPROVE CRITICAL THINKING SKIILS OF JUNIOR HIGH SCHOOL STUDENTS - Febrian Deiza Iva Hananingsih; Budi Jatmiko; Elok Sudibyo (JPPIPA (Jurnal Penelitian Pendidikan IPA), 2021)
This study aims to produce a valid, practical, and effective learning materials with the BW-ExPort learning model to improve the critical thinking skills of junior high school students on heat material. The development of the device uses a modification of the 4D development model with the research design of One Group Pretest and Posttest Design. The research data analyzed were the validity, practicality and effectiveness of learning materials and analyzed quantitatively and qualitatively descriptively. The trial sample was class VII students of SMP Negeri 4 Mojokerto in the odd semester of the 2021/2022 school year, totaling 96 students. The results showed that (a) the learning tools developed had an average syllabus validity of 3.65, lesson plans of 3.63, LKPD of 3.75, teaching materials of 3.75 and test instruments of 3.61 which were categorized as very valid; (b) practical developed learning materials with an average score of 3.68 learning implementation which is in the very good category and student activities in the very good category; (c) the learning materials developed are effective, with the N-Gain value of students' critical thinking skills of 0.71 which is in the high category, the results of the paired t-test from the three experimental classes have a p-value of less than 0.05, and the results of the p-value are less than 0.05. The one-way ANOVA test value is 0.809; (e) the percentage of student responses is 92% with a very good category. The conclusion of learning materials with the BW-ExPort model that was developed properly (valid, practical, and effective) can be used to improve students' critical thinking skills.